Mortality, morbidity and healthcare expenditures after local tumour ablation or partial nephrectomy for T1A kidney cancer. Issue 4 (April 2017) - Larcher, A.; Sun, M.; Dell'Oglio, P.; Trudeau, V.; Boehm, K.; Schiffmann, J.; Tian, Z.; Fossati, N.; Capitanio, U.; Briganti, A.; Montorsi, F.; Karakiewicz, P.
Abstract: Background: Local tumour ablation (LTA) may yield better perioperative outcomes than partial nephrectomy (PN), however the impact of each treatment on perioperative mortality and health care expenditures is unknown. The aim of the study was to compare mortality, morbidity and health care expenditures between LTA and PN. Patients and methods: A population-based assessment of 2471 patients with cT1a kidney cancer treated with either LTA or PN, between 2000 and 2009, in the SEER-Medicare database was performed. After propensity score matching, 30-day mortality, overall and specific complication rates, length of stay, readmission rates and health care expenditures according to LTA or PN were estimated. Multivariable logistic and linear models addressed the effect of each specific LTA approach on overall complication rates, length of stay, readmission rates and health care expenditures. Results: The 30-day mortality was <2% after either LTA or PN (OR 2.27, p = 0.2). The overall complication rate was 21% after LTA and 40% after PN (OR 0.38, p < 0.001). Blood transfusions, infection/sepsis, wound infections, respiratory complications, gastrointestinal complications, acute kidney injury, and accidental puncture or laceration/foreign body left during procedure rates resulted lower after LTA relative to PN (all p < 0.05). Similarly, length of stay and health care expenditures resulted lower after LTA relative to PN (all p < 0.05). Conversely, readmission rate was not significantly different in LTA relative to PN (p = 0.1). Conclusions: Despite similar perioperative mortality, LTA is associated with lower complications rate, shorter length of stay and lower health care expenditure relative to PN.